1977
DOI: 10.1128/iai.18.2.459-466.1977
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia infections in congenitally athymic (nude) mice and in other inbred mouse strains

Abstract: The mortality rate and histopathological features of Nocardia asteroides and Nocardia brasiliensis infections in congenitally athymic (nude) mice of ICR and C3H/eB origins were quite different from what we found for Swiss white mice and other inbred mouse strains (namely, C57/BL/6J, New Zealand Black, BALB/c, CBA/LAC, and C3H/eB). The immunocompetent littermates of the congenitally athymic mice occupied an intermediate position between their athymic siblings and Swiss white mice in terms of their responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Nude mice have no thymus, therefore they serve as an excellent model for determining the roles ofT-lymphocytes in host resistance to Nocardia because these animals are totally deficient in T-cell function (Beaman et al 1978a;Pritchard & Micklem, 1974). N. asteroides, N. brasiliensis and N. caviae have been injected into nude mice by a variety of routes and the mice were then studied extensively (Beaman et al 1978a;Beaman et al 1978b;Beaman & Scates, 1981;Deem et al 1982;Folb, Timme & Horowitz, 1977b). These studies clearly demonstrated that T-lymphocytes played an important role in host immunity to systemic and chronic infections caused by the pathogenic nocardiae.…”
Section: Experimental Infections In Animalsmentioning
confidence: 99%
“…Nude mice have no thymus, therefore they serve as an excellent model for determining the roles ofT-lymphocytes in host resistance to Nocardia because these animals are totally deficient in T-cell function (Beaman et al 1978a;Pritchard & Micklem, 1974). N. asteroides, N. brasiliensis and N. caviae have been injected into nude mice by a variety of routes and the mice were then studied extensively (Beaman et al 1978a;Beaman et al 1978b;Beaman & Scates, 1981;Deem et al 1982;Folb, Timme & Horowitz, 1977b). These studies clearly demonstrated that T-lymphocytes played an important role in host immunity to systemic and chronic infections caused by the pathogenic nocardiae.…”
Section: Experimental Infections In Animalsmentioning
confidence: 99%
“…Previous investigations (6,12) have revealed that athymic mice were more susceptible than their heterozygous littermates or normal mice to challenge with Nocardia, suggesting a role for thymus-derived (T) lymphocytes in protection against Nocardia infection. In the Krick and Remington model, attempts to transfer resist-ance to Nocardia infection by transferring spleen cells from immune to normal mice were unsuccessful when they used doses that had been sufficient for transfer of resistance to other infections (18).…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico about 98% of the cases are produced by actinomycetes, and Nocardia brasiliensis accounts for about 86.6% of the isolates (16). Although the mechanisms of defense against Nocardia are not completely known, some studies indicate that the cellular immune response is very important in resistance (8,12,20,32). Conversely, the role of antibodies is not well established, and their production could even be considered a detrimental factor for the host during N. brasiliensis infection (20).…”
mentioning
confidence: 99%